Rivalry between the Lesotho Defence Force and the Lesotho Mounted Police Service : Causes, Manifestation and Remedy, 1966–2024 - Pherudi, Mokete (Scientia Militaria - South African Journal of Military Studies, 2025)
The end of the Cold War and the post-independence era saw many nations, including Lesotho, bolstering their security apparatus. As part of these efforts, Lesotho undertook reforms within its security forces, including the Lesotho Defence Force, the Lesotho Mounted Police Service, and the National Security Service. These developments led to growing tension between the Lesotho Defence Force and the Lesotho Mounted Police Service, which became arch-rivals following the independence of Lesotho in 1966. This rivalry hindered the two institutions from fulfilling their mandates effectively and professionally. This article reports on the root causes of the conflict between the Lesotho Defence Force and the Lesotho Mounted Police Service, as well as internal divisions within the Lesotho Defence Force itself. The article shows how these tensions have manifested, the measures taken to address them within the security sector, and their broader impact on governance in Lesotho. The discussion concludes with key recommendations for fostering stability and cooperation.